Microbiological Testing for Bacteria Salmonella sp. on Tilapia (Oreochromis niloticus) Using ISO 6579-1:2017 Method at UPTD PPMHP Banten: Pengujian Mikrobiologi Bakteri Salmonella sp. pada Ikan Nila (Oreochromis niloticus) dengan metode ISO 6579-1: 2017 di UPTD PPMHP Banten - Yusmila, Tia; Faustine Elvina Nuryadin, Devi; Ramdani, Ichsanudin (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, IPB University, 2025)
Fish is a food source that is available in large quantities in Indonesia. Indonesia's fisheries production is recorded as occupying the third largest position with total production of 6.43 million tons in the world (FAO 2022). Tilapia is a perishable food so it needs to be handled well so that the freshness of the fish is maintained. The quality of freshness can include appearance, taste, smell and texture which will be consciously or unconsciously assessed by buyers or users of the product. Apart from the freshness and high nutritional value of tilapia, there are aquatic pathogenic microorganisms that can cause disease in humans, for example nausea, diarrhea and stomachache. The presence of microbes in fish can affect quality, such as reducing the freshness of fishery product quality and consumer welfare. Pathogenic bacteria that are often found include Salmonella sp. UPTD PPMH Banten is the organizer of quality control and safety of certified fishery products as well as a quarantine center for microbiological testing of pathogenic bacteria in fishery products, one of which is Salmonella sp. The purpose of the test is to find out the correct testing procedures and according to the procedures, to find out the results of the analysis of Salmonella sp. contamination. on tilapia. Microbiological testing method for Salmonella sp. bacteria. carried out by referring to the standard procedure ISO 6579-1:2017. Results of microbiological testing for Salmonella sp. with the addition of ATCC: 14028 Salmonella Typhi culture in tilapia fish showed positive results for Salmonella sp..